A New Species of Ceropegia L. (Apocynaceae) from Uttarakhand, Western Himalaya, India - Kishor, Kamal; Rawat, Gopal S.; Samant, Sher S. (Phytotaxa, 2022)
A new species of Ceropegia: C. kumaonensis Kamal Kishor, G.S. Rawat & S.S. Samant from Western Himalaya, Kumaon region of Almora District, Uttarakhand, India is described and illustrated. This newly described species differs from its allied taxa C. attenuatula and C. parvissima in having fascicled cymes with multiple drooping flowers per node, flowers without tube, long corolla lobes and having regularly toothed corona.